Challenges and Competencies for Teachers in the 21st Century in the World of Education - Andrefael Rizky Chang; Ahmad Rizaldi; Calvin Samuel (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2026)
Teacher competence is one of the key factors in improving the quality of education in the 21st century. Rapid technological advancements, changing characteristics of students, and the increasing demand for innovative learning require teachers to possess adequate competencies, particularly pedagogical competence, to effectively implement the teaching and learning process. This study aims to examine students' perceptions of the importance of teacher competence, especially pedagogical competence, in addressing the challenges of 21st-century education, identify aspects of pedagogical competence that need to be developed, and analyze the role of pedagogical competence in supporting teacher professionalism. This study employed a quantitative approach using a survey method. Data were collected through a Likert-scale questionnaire consisting of 25 statements distributed to 16 students from the Education Study Program as respondents. The data were analyzed using descriptive statistics in the form of frequencies and percentages. The findings revealed that the majority of respondents selected Agree and Strongly Agree for all the indicators presented. These results indicate that students have positive perceptions of the importance of developing teacher competence, particularly pedagogical competence, as essential preparation for becoming professional teachers. Pedagogical competence is considered crucial for understanding students' characteristics, designing effective learning activities, managing classrooms, integrating educational technology, and enhancing the effectiveness of the teaching and learning process. Therefore, the development of teacher competence, especially pedagogical competence, should be continuously strengthened through university coursework, teaching practicum, and professional training programs to prepare prospective teachers to face the challenges of 21st-century education.